Cardiac remodelling and function with primary mitral valve insufficiency studied by magnetic resonance imaging. (12th January 2016) - Aplin, Mark; Kyhl, Kasper; Bjerre, Jenny; Ihlemann, Nikolaj; Greenwood, John P.; Plein, Sven; Uddin, Akhlaque; Tønder, Niels; Høst, Nis Baun; Ahlström, Malin Glindvad; Hove, Jens; Hassager, Christian; et al.
Abstract: Aims: Evaluation of patients with primary mitral valve insufficiency (MI) is best supported by quantitative measures. Cardiovascular magnetic resonance imaging (CMR) offers flow and cardiac chamber volume quantification. We studied cardiac remodelling with CMR to determine MI regurgitation volumes (MIVol ) related to severe MI. Methods and results: In total, 24, 20, and 28 patients determined to have mild, moderate, and severe primary MI, respectively, were studied. Combining cine stacks with phase-contrast velocity mapping across the ascending aorta, CMR-determined MIVol was reproducibly obtained as the difference between left ventricular (LV) stroke volume and aortic forward flow (Aoflow ). With increasing MI severity, MIVol, left heart volumes, and pulmonary venous diameters increased ( P < 0.01). Severe MI with LV end-systolic diameter of 40 mm was signified by MIVol >40 mL, MI regurgitant fraction >0.30, LV end-diastolic volume (LVEDV(i) ) >108 mL m −2, and a total left heart volume >188 mL m −2 with dilated pulmonary veins and a LVEDV/right ventricular EDV ratio >1.2. In severe MI, LV ejection fraction was unaffected, but the Aoflow and the peak ejection rate indexed to LVEDV were lowered ( P < 0.05). In surgical patients, the MIVol correlated to the decrease in LV dimension after valve surgery ( P < 0.02). Conclusion: CMR provides a reproducible quantitative technique for evaluation of MI, as MIVol and cardiac chamber volumes can be held against diagnostic cut-off values. The Aoflow and peak ejection rate indexed to LVEDV may reveal early LV systolic dysfunction in patients with severe MI. Severe MI is related to lower MI regurgitation volume and fraction than previously believed.